Marine resource abundance drove pre-agricultural population increase in Stone Age Scandinavia - Lewis, J. P.; Ryves, D. B.; Rasmussen, P.; Olsen, J.; van der Sluis, L. G.; Reimer, P. J.; Knudsen, K.-.L.; McGowan, S.; Anderson, N. J.; Juggins, S. (Nature communications, 2020)
How climate and ecology affect key cultural transformations remains debated in the context of long-term socio-cultural development because of spatially and temporally disjunct climate and archaeological records. The introduction of agriculture triggered a major population increase across Europe. However, in Southern Scandinavia it was preceded by ~500 years of sustained population growth. Here we show that this growth was driven by long-term enhanced marine production conditioned by the Holocene Thermal Maximum, a time of elevated temperature, sea level and salinity across coastal waters. We identify two periods of increased marine production across trophic levels (P1 7600–7100 and P2 6400–5900 cal. yr BP) that coincide with markedly increased mollusc collection and accumulation of shell middens, indicating greater marine resource availability. Between ~7600–5900 BP, intense exploitation of a warmer, more productive marine environment by Mesolithic hunter-gatherers drove cultural development, including maritime technological innovation, and from ca. 6400–5900 BP, underpinned a ~four-fold human population growth. How the development of human societies is influenced through their ecological environment and climatic conditions has been the subject of intensive debate. Here, the authors present multi-proxy data from southern Scandinavia which suggests that pre-agricultural population growth there was likely influenced by enhanced marine production.